Factors Affecting The Demand For Tilapia Fish (oreochromis niloticus) At Tanjung Market, Tabalong Regency - Nelly Anderiyani; Irma Febrianty; Achmad Syamsu Hidayat (International Journal of Science and Environment (IJSE), 2026)
The demand for Tilapia fish is not determined only by food needs. Consumers also consider price, fish freshness quality, household income, family size, market access, and consumption habits. This study aimed to analyze consumer characteristics and the factors affecting the demand for Tilapia fish at Tanjung Market, Tabalong Regency. This topic is important because Tanjung Market is a center of food trade and Tilapia fish is a widely consumed source of animal protein among households. The study used a descriptive quantitative approach supported by multiple linear regression analysis. A total of 96 consumers were selected through accidental sampling based on age, willingness to be interviewed, and the purchase of Tilapia fish during the study period. Data were collected through observation, structured interviews, questionnaires, and documentation. The research variables included fish price, fish quality as a dummy variable, consumer income, family size, and the quantity of Tilapia fish demanded. The results showed that respondents were dominated by bachelor’s degree graduates at 30.2%, employees at 24.0%, residents of Belimbing at 27.1%, and married respondents at 55.2%. All respondents stated that psychographic aspects, income effects, market access, and proximity to the market influenced purchasing decisions. The regression model fulfilled the classical assumptions, with a normality significance value of 0.058, no multicollinearity, a Durbin-Watson value of 2.091, and no heteroscedasticity. The R Square value of 0.538 indicated that the model explained 53.8% of the variation in Tilapia fish demand. The F-test produced an F-value of 26.469 with a significance level of <0.001. Partially, only price had a negative and significant effect on Tilapia fish demand, with a coefficient of -0.000045, a t-value of -10.189, and a significance level of <0.001. Fish quality as a dummy variable, income, and family size did not have significant partial effects. Consumers at Tanjung Market were highly price-sensitive in determining the quantity of Tilapia fish purchased.